Global Monitoring Report 2012 : Food Prices, Nutrition, and the Millennium Development Goals - World Bank (Washington, DC: World Bank, 2012)
Every year, the Global Monitoring Report (GMR) gauges progress across the Millennium Development Goals (MDGs), so we can better understand whether we are delivering on basic global needs. These needs include affordable, nutritious food; access to health services and education; and the ability to tap natural resources sustainably whether clean water, land for urban expansion, or renewable energy sources. We assess how well the world is doing by looking at income poverty, schooling levels, the health of mothers and children, and inroads in treating HIV/AIDS, malaria, and tuberculosis, as well as assessing how the international development community delivers aid. We also try to measure levels of malnutrition and hunger in the world. Food prices can affect all these indicators. For these reasons, the Global Monitoring Report 2012 takes the theme of 'food prices, nutrition, and the MDG.' This year's edition highlights the need to help developing countries deal with the harmful effects of higher and more volatile food prices. The 2012 GMR addresses these basic questions. It summarizes effects of food prices on several MDGs. It reviews policy responses including domestic social safety nets, nutritional programs, agricultural policies, regional trade policies, and support by the international community. And it outlines future prospects.